Meningkatkan Green Purchasing Behavior di Kota Kupang: Peran Green Perceived Value, Green Perceived Risk, dan Green Perceived Trust - Lopes Amaral, Maria Augustin; Adrianus, Jou Sewa; Watu, Engelbertus G. Ch. (Jurnal Manajemen, 2024)
The aim of this study is to develop a preliminary framework to explore the ecological influence of perceived ecological value, perceived risk, social influence, and low price sensitivity on environmentally friendly purchase intentions and discuss the mediating role of environmentally friendly beliefs. Furthermore, this research uses empirical research through a questionnaire survey method to verify the hypothesis and explore its managerial potential. Data processing uses structural equation modeling (SEM) to verify the research framework. Empirical results show that awareness of environmentally friendly values, social influence and sensitivity to low prices have a positive impact on environmentally friendly beliefs and environmentally friendly purchasing intentions, while green ro risk perception has no impact at all. Furthermore, this research shows that the relationship between green purchase intentions and perceived green value is moderated by green beliefs. Therefore, invest resources to increase the perceived value of environmental compassion to increase environmental compassion beliefs and environmentally friendly purchasing intentions. This study summarizes the literature on green marketing and relationship marketing within a new management framework of green purchase intentions. This study uses five new concepts – perceived green value, social influence, low price sensitivity, green beliefs, and green purchase intentions – to develop an original research framework for increasing green shopping intentions. Although previous research has highlighted issues related to purchasing intentions, no research has yet explored issues related to environmentally friendly management. Therefore, this article builds a research framework to address green purchase intentions.